Genistein at Maximal Physiologic Serum Levels Induces G0/G1 Arrest in MCF-7 and HB4a Cells, But Not Apoptosis - Tsuboy, Marcela S. [UNESP]; Marcarini, Juliana C. [UNESP]; Souza, Alecsandra O. de; Paula, Natalia A. de; Dorta, Daniel J.; Mantovani, Mario S.; Ribeiro, Lucia R. [UNESP] (Mary Ann Liebert, Inc., 2014)
Several studies have demonstrated that a balanced diet can contribute to better human health. For this reason, soy-based food and pure isoflavones (pills) are one of the most consumed. The association of this consumption and lower risks of chronic diseases and cancer is well established for the Asian population and has been attracting thw attention of people worldwide, especially women at menopause who seek to alleviate the symptoms associated with the lack of estrogen. Despite positive epidemiological data, concerns still exist because of conflicting results found in scientific literature with relation to the role of isoflavones in breast and hormone-related cancers. The aim of our study was to investigate the cytotoxicity, induction of apoptosis, and changes in apoptosis-related genes of maximal physiological serum levels of the isoflavone genistein (Gen) in MCF-7 tumoral cells and in HB4a non-tumoral cells. In addition, induction of cell cycle arrest was also investigated. Only supraphysiological levels of Gen (50 and 100M) were cytotoxic to these cell lines. Concentrations of 10 and 25M did not induce apoptosis and significant changes in expression of the studied genes. Positive results were found only in cell cycle analysis: G0/G1 delay of MCF-7 cells in both concentrations of Gen and at 25M in HB4a cells. It is the first study investigating effects of Gen in the HB4a cell line. Thus, despite the lack of apoptosis induction (generally found with high concentrations), Gen at physiologically relevant serum levels still exerts chemopreventive effects through the modulation of cell cycle.
Keywords: breast cell lines; cancer chemoprevention; cell cycle; cell death; physiological concentration; soy isoflavone